Alterations in bile acids as metabolic signatures in the patients with human adenovirus type 7 infection - Xu, Wen; Du, Juan; Wei, Ting-Ting; Chen, Lin-Yi; Yang, Xin-Xin; Bo, Tu; Liu, Han-Yu; Xie, Ming-Zhu; Zhao, Tian-Shuo; Yang, Jun-Lian; Cui, Fuqiang; Chen, Wei-Wei; et al. (Frontiers in Medicine, 2022)
Objectives The changes in metabolism by human adenovirus (HAdV) infection was unclear. The potential mechanism of HAdV-7 causing acute respiratory tract infection was explored. Methods Totally 35 patients with HAdV-7 infection, 32 asymptomatic cases with HAdV-7 and 14 healthy controls were enrolled from an outbreak of HAdV-7 in the army. The serum samples were analyzed by untargeted and targeted metabolomics. Then we verified the effects of differential metabolites on HAdV-7 replication in an A549 cell line. Results The untargeted metabolomics analysis revealed more significant changes in the classes of sphingolipids, polyketides, glycerolipids, fatty acyls, and carboxylic acids and their derivatives in the patients with HAdV-7 than in healthy controls. Two key metabolic pathways of secondary and primary bile acid biosynthesis were noted from pathway enrichment analysis. Targeted metabolomics analysis showed that the levels of unconjugated bile acids in the patients were significantly lower, while the levels of glyco- and tauro- conjugated bile acids in patients and asymptomatic cases were higher than those in the healthy controls. The profiles of cytokines and peripheral lymphocyte subsets obviously varied at different levels of bile acids, with significant differences after HAdV-7 infection. a cell verification test demonstrated that the replication of HAdV-7 was significantly reduced when GCDCA and TCA were added. Conclusions Bile acids inhibited HAdV-7 replication ex vivo. Alterations in bile acids play a protective role in metabolic signatures in the patients with HAdV-7 infection.